Economic impact of the first pass effect in mechanical thrombectomy for acute ischaemic stroke treatment in Spain: a cost-effectiveness analysis from the national health system perspective. Issue 9 (1st September 2022) - González Diaz, Eva; Rodríguez-Paz, Carlos; Fernandez-Prieto, Andres; Martínez-Galdámez, Mario; Martínez-Moreno, Rosa; Ortega Quintanilla, Joaquín; Tomasello, Alejandro; Zamarro, Joaquín; Liebeskind, David; Zaidat, Osama O; Mueller-Kronast, Nils H
Abstract : Objective: The mechanical thrombectomy (MT) benefit is related to the degree of reperfusion achieved. First pass effect (FPE) is defined as complete/near revascularisation of the large-vessel occlusion (modified Thrombolysis in Cerebral Infarction (mTICI) 2c-3) after a single device pass. This study assessed the health benefit and economic impact of achieving FPE for acute ischaemic stroke (AIS) patients from the Spanish National Health System (NHS) perspective. Design: A lifetime Markov model was used to estimate incremental costs and health outcomes (measured in quality-adjusted life-years (QALYs)) of patients that achieve FPE. A subanalysis of the Systematic Evaluation of Patients Treated With Neurothrombectomy Devices for Acute Ischaemic Stroke (STRATIS) registry was performed to obtain clinical outcomes. The base case included all patients that achieved at least a final mTICI ≥2 b, while the alternative scenario included all patients regardless of their final mTICI (0–3). Treatment costs were updated to reflect current practice based on expert panel consensus, while other acute and long-term costs were obtained from a previous cost-effectiveness analysis of MT performed in Spain. Sensitivity analyses were performed to assess the model's robustness. Setting: Spanish healthcare perspective. Participants: AIS patients in Spain. Interventions: FPE following MT. Outcome measures: The model estimated QALYs, lifetime costs and net monetary benefit for the FPE and non-FPE group, depending on the inclusion of reperfusion groups and formal care costs. Results: STRATIS subanalysis estimated significantly better clinical outcomes at 90 days for the FPE group in all scenarios. In the base case, the model estimated lifetime cost saving per patient of €16 583 and an incremental QALY gain of 1.2 years of perfect health for the FPE group. Cost savings and QALY gains were greater in the alternative scenario (-€44 289; 1.75). In all scenarios, cost savings were driven by the long-term cost reduction. Conclusion: Achieving FPE after MT can lead to better health outcomes per AIS patient and important cost savings for the Spanish NHS.